Establishing Reliability and Validity of a High Leverage Practice Rubric for Assessment (HLPR-A) - Deana J. Ford; Sara E. Luke; S. Michelle Vaughn (Universitas Riau, 2022)
The purpose of the current research study was to establish reliability and validity of an assessment high-leverage practice rubric (HLPR-A). Five raters scored 33 participants’ instructional videos two times using the HLPR-A. Interrater and intrarater reliability was established using an intraclass correlation coefficient. Content validity was established through expert review. Construct validity was presented using a nomological network. Internal validity was confirmed using principal axis factor analysis. The results revealed the HLPR-A to be a reliable and valid tool for assessing preservice teachers’ performance when interpreting and communicating assessment information to a parent during a parent-teacher conference using mixed reality virtual simulations. Future research could explore using the HLPR-A on other populations, with a variety of raters, in other environments, and programs.